Consideration Set Formation with Multiproduct Firms: The Case of Within-Firm and Across-Firm Evaluation Costs - Liu, Lin; Dukes, Anthony (Management Science, 2013)
We consider a theoretical setting in which firms carry multiple products and consumers incur evaluation costs not only across firms but also within firms. Consumers judiciously decide the number of firms to include in their consideration sets as well as how many products from those firms. This decision depends on the relative trade-offs of evaluating an additional product and whether it is from a firm already included in the consideration set or from an entirely new firm. The composition of consumers' consideration set affects how firms compete in prices and in the number of products to offer. Contrary to previous literature, we find that firm differentiation can reduce firms' product lines and within-firm evaluation costs have either a positive or a negative effect on firms' prices. Interestingly, we show that within-firm evaluation costs and across-firm evaluation costs are different constructs. The number of products firms offer in equilibrium can exceed the socially optimal level if within-firm evaluation costs are significant. This paper was accepted by J. Miguel Villas-Boas, marketing.